2016
DOI: 10.1371/journal.pone.0167048
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Duration, Exercise, Shift Work and Polycystic Ovarian Syndrome-Related Outcomes in a Healthy Population: A Cross-Sectional Study

Abstract: ContextFew studies have examined the associations between sleep duration, shiftwork, and exercise to the infrequent menstruation, hyperandrogenism, and ovarian morphological changes observed in women with polycystic ovarian syndrome (PCOS).ObjectiveTo examine whether lifestyle factors, including short sleep duration, insufficient exercise, and shiftwork, alone or in combination, are associated with the reproductive and metabolic abnormalities typical of PCOS in a healthy population.Study Design, Size, Duration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 29 publications
1
52
1
2
Order By: Relevance
“…Women with at least one ovarian cyst or follicle exceeding a diameter of 10 mm, even after repeated evaluation in their following cycle, were excluded to eliminate the possibility of a spuriously large ovarian volume and endocrine effects from a developing dominant follicle. Derivation of antral follicle counts and ovarian volume were as described previously …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Women with at least one ovarian cyst or follicle exceeding a diameter of 10 mm, even after repeated evaluation in their following cycle, were excluded to eliminate the possibility of a spuriously large ovarian volume and endocrine effects from a developing dominant follicle. Derivation of antral follicle counts and ovarian volume were as described previously …”
Section: Methodsmentioning
confidence: 99%
“…Physical measurements included height, weight, waist circumference and blood pressure. Glucose, insulin and lipids (cholesterol, triglycerides, high‐density lipoprotein [HDL] and low‐density lipoprotein [LDL]) were measured as described previously . Body mass index (BMI), waist to hip ratio (WHR), the homoeostasis model assessment‐estimated insulin resistance (HOMA‐IR) and presence of metabolic syndrome were determined from those measurements as described previously …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Weight reduction through diet control therapy, was adopted in the current study as obesity play a significant role in the pathology of PCOS [6], and though conservative treatment is recommended for PCOS through lifestyle modification [17], the term lifestyle modification is somehow vague. Lim et al [20], reported their disagreement with such hypothesis concerning the association between the lack of exercise and the clinical or biochemical characteristics typical of PCOS, supporting the concept of weight reduction in favor of exercise in the field of lifestyle modification. Many studies support our results concerning the positive effects of weight reduction on obese PCOS women [18][19][21][22], which is further supported by studying the eating habits of PCOS women compared to controls; Adult PCOS women tend to eat between meals and adolescents PCOS tend to have non healthy snacks which may intensify the phenotype of PCOS.…”
Section: Discussionmentioning
confidence: 99%